PENGARUH BEBAN KERJA DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI DENGAN STRESS KERJA SEBAGAI VARIABEL MEDIASI KARYAWAN - Mei Ie; Henny Henny; Adwin Anugrah Kevin; Angel Wangsa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Organizational commitment is an important factor to determine the level of production and the success of an organization in achieving its goals. Factors that can play a role in increasing or decreasing organizational commitment are workload, job satisfaction, and work stress. The purpose of this study was to determine how the influence of workload and job satisfaction on organizational commitment with the mediating variable of work stress. Sampling in this study using the total sampling method. The samples taken for this study were 40 employees of PT XYZ who are engaged in oil-gas manufacturing. The research data was taken with a questionnaire/questionnaire instrument using an ordinal scale. The research data is processed using SmartPLS, the results of this study indicate that workload has a negative and insignificant effect on organizational commitment, job satisfaction has a positive and insignificant effect on organizational commitment, work stress has a negative and insignificant effect on organizational commitment, workload has no significant effect on organizational commitment. and not significant on organizational commitment mediated by work stress, and job satisfaction has no significant and insignificant effect on organizational commitment mediated by job stress. This study suggests that companies should give more appropriate tasks to workers according to the position they are carrying out so as not to burden workers with excessive assignments so that many tasks are piled up and workers feel very burdened with work that should not be their job, increasing comfort. and security to employees in order to achieve job satisfaction, then provide positive activities outside of work to relieve work stress experienced by workers within the company.